An exceptional series of phase transitions in hydrophobic amino acids with linear side chains - Görbitz, Carl Henrik; Karen, Pavel; Dušek, Michal; Petříček, Václav (IUCrJ, 2016)
The solid-state phase transitions and intermediate structures of S-2-amino-butanoic acid (l-2-aminobutyric acid), S-2-aminopentanoic acid (l-norvaline), S-2-aminohexanoic acid (l-norleucine) and l-methionine between 100 and 470 K, identified by differential scanning calorimetry, have been characterized in a comprehensive single-crystal X-ray diffraction investigation. Unlike other enantiomeric amino acids investigated until now, this group featuring linear side chains displays up to five distinct phases. The multiple transitions between them involve a number of different processes: alteration of the hydrogen-bond pattern, to our knowledge the first example of this observed for an amino acid, sliding of molecular bilayers, seen previously only for racemates and quasiracemates, concerted side-chain rearrangements and abrupt as well as gradual modifications of the side-chain disorder. Ordering of l-norleucine upon cooling even proceeds via an incommensurately modulated structure. l-Methionine has previously been described as being fully ordered at room temperature. An accurate refinement now reveals extensive disorder for both molecules in the asymmetric unit, while two previously unknown phases occur above room temperature.
Keywords: side-chain stacking; disorder; amino acids; polymorphism; phase transitions; hydrogen bonding; modulated phases; molecular crystals